Crafting the divine: How metaphors shape religious language - Hasselbaink, Jacob Floyd (Journal of Religion and Linguistics, 2025)
This research investigates the various purposes of metaphors in religious discourse. We will investigate the extent to which we can understand metaphorical language as irreducible. First, we will assert that metaphors convey more than just propositional contents. Their goals also frame their imagistic perspective that cannot be limited to a literal paraphrase. Moreover, in situations where plain language fails, they employ metaphors to bridge expression gaps. A detailed metaphorical concept will clarify the function of catachresis. With those metaphors, we can communicate things that we cannot conceptually isolate from a given utterance. Thus, with such analogies, we can transcend the boundaries of our conceptual repertory, which is absolutely essential for religious language. Finally, the results of the previous discussions about how metaphors can't be changed will be looked at in light of the radical view that all statements about God are inherently and irreducibly metaphorical if they are taken seriously.